The Effect of Health Education in Postpartum Mothers on Colostrum on the Intensity of Early Breasfeeding in Newborn Babies - Uswatun Hasanah Rowi; Novita Novita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: To determine the effect of health education on mothers about colostrum with the intensity of early breastfeeding. Methods: Quasi-experimental with one group pretest-posttest design. Education was delivered for one week consisting 3 session and 90 minutes for each session Sample of this study was mothers who have newborn baby and willing to participate in this study. Result: The Colostrum Correlation value is 0.542 with a p-value of 0.000, there is a relationship between the Pre-test Colustrum variable and the Post-test realized. The correlation between breastfeeding is 0.624 with a p-value of 0.000, there is a relationship between the pre-test and post-test variables of breastfeeding. Conclusion: There is a relationship between the frequency of colostrum measurements with breastfeeding before and after the intervention